MOS2 / MOO3 / MXENE three-component mesoporous composite nanomaterial and application thereof

CN122992031APending Publication Date: 2026-10-27ANYANG INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611180894.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

(1)复合方式以两相复合为主,缺乏三相协同效应的充分利用;

Benefits of technology

(1)工艺简单,一步完成:采用一步水热法,无需多步反应或额外的后处理工序,显著降低了制备成本和时间。四种原料在同一反应体系中同步完成的生成以及MXene的复合嵌入,操作简便,适合规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992031A_ABST
    Figure CN122992031A_ABST
Patent Text Reader

Abstract

The application discloses a three-component mesoporous composite nanomaterial and a preparation method and application thereof. The composite nanomaterial is in a nanoparticle form, has 2-10 nm mesopores in the interior, is formed by three-phase compounding, MXene is coated on the particle surface and partially embedded in the particle interior, and a heterojunction interface is formed between the three phases. The preparation method is as follows: sodium molybdate dihydrate, thiourea, glucose and MXene are dispersed in water, hydrochloric acid is used to adjust the pH to 0.5-1.5, and the water is hydrothermally reacted at 180-220 DEG C for 12-36 h, and then the composite nanomaterial is obtained through cooling, separation, washing and drying. The material can be used as a lithium ion battery or a sodium ion battery negative active material, and has the characteristics of simple preparation process, short ion transmission path and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage materials technology, specifically relating to an electrode material for use in lithium-ion batteries, sodium-ion batteries, or supercapacitors. Three-component mesoporous composite nanomaterials and their applications. Background Technology

[0002] Lithium-ion batteries (LIBs) have become the mainstream power source due to their high energy density and long cycle life. However, lithium resources are limited and prices are rising. Sodium-ion batteries (SIBs) have attracted widespread attention due to the abundance and low cost of sodium. However, sodium ions have a larger radius, and their storage mechanism is more complex. Existing anode materials generally suffer from problems such as low capacity and poor cycle stability.

[0003] Transition metal oxides / sulfides such as With high theoretical capacity and abundant resource reserves, it is widely used as a negative electrode material for lithium / sodium ion batteries. It has a typical layered structure, which is conducive to ion insertion and extraction, but its intrinsic conductivity is low and its volume changes significantly during charge and discharge. MoO3 has high theoretical capacity and is environmentally friendly, but it also suffers from low conductivity and severe volume effects. MXene, as a novel two-dimensional transition metal carbide / nitride material, has excellent metallic conductivity and good mechanical properties, and is considered an ideal electrode material matrix.

[0004] Therefore, researchers attempted to Composites with MXene can improve electrochemical performance. For example, CN109830675A discloses a composite material for anodes in lithium-ion batteries. Composite material preparation method, using spin coating to... Composite with MXene; CN116334650A discloses a Composite materials were prepared via a multi-step method and applied to the catalytic hydrogen evolution process in water electrolysis; another patent has also been disclosed. Electrode materials and their preparation methods are applied to zinc-ion batteries. However, the existing technology still has the following shortcomings: (1) The composite method is mainly two-phase composite, lacking Full utilization of the three-phase synergistic effect; (2) The active substances in the composite material are prone to agglomeration, the active sites are not sufficiently exposed, and there is a lack of reasonable mesoporous structure design; (3) Existing composite materials still have considerable room for improvement in terms of high-rate performance and long-cycle stability; (4) The preparation process involves multiple steps of reaction, which is complex and has poor controllability.

[0005] Therefore, it is necessary to develop a novel structure, simple preparation process, good mesoporous structure, and three-phase synergistic effect. Composite nanomaterials are of great significance for improving the electrochemical performance of lithium / sodium-ion batteries and supercapacitors. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a... Three-component mesoporous composite nanomaterials and their applications. This composite material, synthesized via a one-step hydrothermal method, exhibits an internal mesoporous structure, homogeneous three-phase composite, and a combination of MXene coating and embedding, demonstrating excellent electrochemical energy storage performance.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a... A three-component mesoporous composite nanomaterial, wherein the composite nanomaterial is in the form of nanoparticles, composed of... The three-phase composite is formed and has a mesoporous structure with a pore size of 2 to 10 nm. The specific surface area of ​​the composite nanomaterial is 7.8 m² / g.

[0008] (1) Mix 2.0 g sodium molybdate dihydrate, 4.0 g thiourea, 1.0 g glucose and 0.2 g... The powder was added to 40 mL of deionized water and magnetically stirred for 30 min to obtain a mixed solution; (2) Under stirring conditions, the pH of the mixed solution is adjusted to 1.0 using hydrochloric acid with a concentration of 1.0 mol / L; (3) Transfer the pH-adjusted mixed solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally react at 200 °C for 24 h. (4) After the hydrothermal reaction is complete, the mixture is allowed to cool naturally to room temperature. The resulting product is then separated, washed, and dried to obtain the product described above. Three-component mesoporous composite nanomaterials.

[0009] Preferably, in step (4), the product is separated by centrifugation at a speed of 8000 r / min for 5 min each time; the product is washed alternately with deionized water and anhydrous ethanol, each washing 3 times; the washed product is then vacuum dried at 70°C for 15 h.

[0010] Preferably, the A lithium-ion battery negative electrode sheet made of three-component mesoporous composite nanomaterials includes a copper foil current collector and an active material layer disposed on the surface of the copper foil current collector, wherein the active material layer includes the... The three-component mesoporous composite nanomaterial, conductive carbon black, and polyvinylidene fluoride are present in a mass ratio of 8:1:1.

[0011] Preferably, the CR2032 type lithium-ion coin cell with a lithium-ion battery negative electrode further includes a lithium metal sheet, a Celgard 2400 type separator, and an electrolyte; the lithium-ion battery negative electrode is the working electrode, and the lithium metal sheet is the counter electrode; the electrolyte has a concentration of 1 mol / L. The electrolyte is composed of ethylene carbonate and dimethyl carbonate in a 1:1 volume ratio.

[0012] Preferably, A sodium-ion battery negative electrode sheet made of three-component mesoporous composite nanomaterials includes an aluminum foil current collector and an active material layer disposed on the surface of the aluminum foil current collector, wherein the active material layer includes the... The three-component mesoporous composite nanomaterial, conductive carbon black, and sodium carboxymethyl cellulose are present in a mass ratio of 7:2:1.

[0013] Preferably, the CR2032 type sodium-ion coin cell with sodium-ion battery negative electrode further includes a metallic sodium sheet, a glass fiber separator, and an electrolyte; the sodium-ion battery negative electrode is the working electrode, and the metallic sodium sheet is the counter electrode; the electrolyte has a concentration of 1 mol / L. The electrolyte, wherein the solvent of the electrolyte is composed of ethylene carbonate and propylene carbonate in a 1:1 volume ratio, and the electrolyte contains 5% by mass of fluoroethylene carbonate. Compared with the prior art, the present invention has the following beneficial effects: (1) Simple process, completed in one step: The one-step hydrothermal method eliminates the need for multiple reaction steps or additional post-processing, significantly reducing preparation costs and time. The four raw materials are reacted simultaneously in the same reaction system. The generation of MXene and its composite embedding are simple to operate and suitable for large-scale production.

[0014] (2) The key role of pH regulation: pH regulation is the core of the thermodynamics and kinetics for achieving controllable coexistence of the two phases in this system. When the system pH≈1.0, on the one hand, the strong acid environment moderately inhibits the decomposition kinetics of thiourea, allowing for the slow release of hydrogen sulfide and precisely limiting the molybdenum source to... The transformation process; on the other hand, this acidity precisely meets the thermodynamic threshold of molybdate protonation condensation, driving the in-situ dehydration of the molybdenum source that did not participate in the sulfidation reaction into... By precisely balancing the reaction rates of these two competing pathways, [this was achieved]. Controllable co-precipitation of two phases at the nanoscale.

[0015] (3) Unique mesoporous structure: The product has mesopores of 2–10 nm with a concentrated pore size distribution, which ensures sufficient electrolyte wetting and rapid ion transport while avoiding high specific surface area (>50 nm). 2 The increased side reactions and decreased initial coulombic efficiency caused by ( / g) are problems. The specific surface area is moderate (7–10 m²). 2 / g), which is beneficial for the formation of a stable solid electrolyte interface (SEI) film.

[0016] (4) The core effect of three-phase synergy: This invention achieves , In-situ recombination and functional division of labor with MXene three phases It provides high theoretical capacity and layered ion channels. MXene contributes additional pseudocapacitive charge storage and constructs a conductive framework and structural support. The tight heterogeneous interface formed between the three phases induces electron redistribution, accelerates interfacial charge transfer, and reduces electrochemical impedance, thereby significantly improving electrode reaction kinetics. The synergistic gains of the three phases in capacity contribution, electron transport, and structural stability result in a leapfrog improvement in the overall electrochemical performance of the composite material.

[0017] (5) Excellent electrochemical performance: When the composite nanomaterial is used as the negative electrode active material of lithium-ion battery, the initial discharge specific capacity at a current density of 0.1 A / g is 1000-1200 mAh / g, and the reversible capacity after 400 cycles at 1 A / g can reach more than 1100 mAh / g. When the composite nanomaterial is used as the negative electrode active material of sodium-ion battery, the reversible capacity after 400 cycles at 0.5 A / g can reach more than 1500 mAh / g. Attached Figure Description

[0018] Figure 1 In Embodiment 1 of the present invention Scanning electron microscope image of three-component mesoporous composite nanomaterials; Figure 2 In Embodiment 1 of the present invention High-resolution transmission electron microscopy (TEM) image of the three-component mesoporous composite nanomaterial. The image shows... The (002) crystal plane, The (041) crystal plane of MXene and the (002) crystal plane of MXene; Figure 3 In Embodiment 1 of the present invention The three-component mesoporous composite nanomaterials and Comparative Example 1 The N2 adsorption-desorption isotherms and pore size distribution curves of the two-component material indicate that The three-component mesoporous composite nanomaterials have a larger specific surface area, larger pore volume, and most probable pore size; Figure 4 In Embodiment 1 of the present invention The three-component mesoporous composite nanomaterial and Comparative Example 1 Cyclic performance curves of the two-component material as a negative electrode material for lithium-ion batteries at a current density of 1 A / g.

[0019] Figure 5 In Example 1 Cyclic performance curves of three-component mesoporous composite nanomaterials as anode materials for sodium-ion batteries at a current density of 0.5 A / g. Detailed Implementation

[0020] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. However, the embodiments do not limit the scope of the invention in any way. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0021] The present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited to the following embodiments. Example 1

[0022] (1) Preparation of composite nanomaterials Weigh 2.0 g of sodium molybdate dihydrate ( ), 4.0 g thiourea, 1.0 g glucose and 0.2 g Add the powder to 40 mL of deionized water and stir magnetically for 30 min to mix it evenly.

[0023] Under stirring conditions, the pH of the mixed solution was adjusted to 1.0 using 1.0 mol / L hydrochloric acid. The resulting mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, sealed, and placed in an oven at 200 °C for 24 h.

[0024] After the reaction was completed, the product was allowed to cool naturally to room temperature. The product was then centrifuged and washed three times each with deionized water and anhydrous ethanol, with a centrifugation speed of 8000 r / min and a centrifugation time of 5 min each time.

[0025] The washed product was placed in a vacuum drying oven and dried at 70°C for 15 h to obtain a black powder. Three-component mesoporous composite nanomaterials.

[0026] (2) Material characterization The composite nanomaterials prepared in Example 1 were characterized.

[0027] like Figure 1As shown, the resulting composite material exhibits a nanoscale particle morphology with relatively uniform particle size.

[0028] like Figure 2 As shown, it can be observed in the composite material. (002) crystal plane, The (041) crystal plane and the (002) crystal plane of MXene indicate that A three-component composite structure is formed.

[0029] like Figure 3 As shown, the specific surface area of ​​the obtained composite material is 7.8 m² / g, and the pore size is mainly distributed in the range of 2 to 10 nm.

[0030] (3) Lithium-ion battery performance testing The results Composite nanomaterials, conductive carbon black, and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone was added to form a slurry. The slurry was then coated onto copper foil, vacuum dried, and cut into electrode sheets. The electrode sheets were then vacuum dried at 80°C for 12 h and cut into circular pieces with a diameter of 12 mm.

[0031] Using the prepared electrode sheet as the working electrode, a lithium metal sheet as the counter electrode, and Celgard 2400 as the diaphragm, at a concentration of 1 mol / L... A mixed solution of ethylene carbonate and dimethyl carbonate was used as the electrolyte, with a volume ratio of ethylene carbonate to dimethyl carbonate of 1:1. CR2032 button cells were assembled in an argon-filled glove box.

[0032] Constant current charge-discharge tests were conducted within a voltage range of 0.01–3.0 V. Test results show that at a current density of 0.1 A / g, the initial reversible specific capacity is 1134 mAh / g; Figure 4 As shown, after 400 cycles at a current density of 1 A / g, the reversible capacity is 1141 mAh / g.

[0033] (4) Sodium-ion battery performance test The results Composite nanomaterials, conductive carbon black, and sodium carboxymethyl cellulose were mixed in a mass ratio of 7:2:1, and deionized water was added to grind them into a slurry. The slurry was coated onto aluminum foil, vacuum dried, and then cut into electrode sheets. The sheets were vacuum dried at 80°C for 12 h and then cut into round sheets with a diameter of 12 mm.

[0034] Using the obtained electrode sheet as the working electrode, the metallic sodium sheet as the counter electrode, and glass fiber as the diaphragm, at 1 mol / L A mixed solution of ethylene carbonate and propylene carbonate was used as the electrolyte, with a volume ratio of ethylene carbonate to propylene carbonate of 1:1. 5% fluoroethylene carbonate was added, and CR2032 button cells were assembled in an argon-filled glove box.

[0035] A constant current charge-discharge test was performed within a voltage range of 0.01–3.0 V. For example... Figure 5 As shown, after 400 cycles at a current density of 0.5 A / g, the reversible capacity is 1786 mAh / g. Example 2

[0036] Weigh out 1.0 g of sodium molybdate dihydrate, 2.0 g of thiourea, 0.5 g of glucose, and 0.1 g of... Add the powder to 50 mL of deionized water and ultrasonically stir for 20 min to mix it evenly.

[0037] The pH of the mixed solution was adjusted to approximately 1.0 using 1.0 mol / L hydrochloric acid, and then the mixed solution was transferred to a hydrothermal reactor and reacted at 180 °C for 36 h.

[0038] After the reaction was completed, the mixture was allowed to cool naturally to room temperature. After centrifugation, washing with deionized water and anhydrous ethanol three times each, and drying, the desired product was obtained. Three-component mesoporous composite nanomaterials. Comparative Example 1

[0039] The composite material was prepared according to the method of Example 1, except that MXene was not added, and only sodium molybdate dihydrate, thiourea, and glucose were used as raw materials. The other preparation conditions were the same as in Example 1. Two-component composite material.

[0040] The results The two-component composite material was tested according to the electrode preparation method and lithium-ion battery test conditions described in Example 1. Figure 4 As shown, after 400 cycles at a current density of 1 A / g, the reversible capacity is 750 mAh / g, which is lower than the reversible capacity of the three-component composite material obtained in Example 1. Comparative Example 2

[0041] The composite material was prepared according to the method of Example 1, except that hydrochloric acid was not used to adjust the pH of the mixed solution, and the pH of the mixed solution was about 6 to 7. The other preparation conditions were the same as in Example 1.

[0042] The main products obtained are The complex with MXene did not form a significant [unclear] The phase is characterized by poor mesoporous structure.

[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Equivalent substitutions or conventional adjustments made by those skilled in the art based on the present invention should all be included within the scope of protection of the present invention.

Claims

1. A kind The three-component mesoporous composite nanomaterial is characterized by... The composite nanomaterial is in the form of nanoparticles, consisting of... The three-phase composite is formed and has a mesoporous structure with a pore size of 2 to 10 nm. The specific surface area of ​​the composite nanomaterial is 7.8 m² / g.

2. The one described in claim 1 The method for preparing three-component mesoporous composite nanomaterials is characterized by... Includes the following steps: (1) Mix 2.0 g sodium molybdate dihydrate, 4.0 g thiourea, 1.0 g glucose and 0.2 g... The powder was added to 40 mL of deionized water and magnetically stirred for 30 min to obtain a mixed solution; (2) Under stirring conditions, the pH of the mixed solution is adjusted to 1.0 using hydrochloric acid with a concentration of 1.0 mol / L; (3) Transfer the pH-adjusted mixed solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor and hydrothermally react at 200 °C for 24 h. (4) After the hydrothermal reaction is complete, the mixture is allowed to cool naturally to room temperature. The resulting product is then separated, washed, and dried to obtain the product described above. Three-component mesoporous composite nanomaterials.

3. The preparation method according to claim 2, characterized in that, In step (4), the product was separated by centrifugation at a speed of 8000 r / min for 5 min each time. The product was washed alternately with deionized water and anhydrous ethanol, with each washing being 3 times. The washed product was then vacuum dried at 70°C for 15 h.

4. A method employing the method described in claim 1 A lithium-ion battery anode sheet made of three-component mesoporous composite nanomaterials, characterized in that... It includes a copper foil current collector and an active material layer disposed on the surface of the copper foil current collector, the active material layer comprising the... The three-component mesoporous composite nanomaterial, conductive carbon black, and polyvinylidene fluoride are present in a mass ratio of 8:1:

1.

5. A CR2032 type lithium-ion coin cell using the lithium-ion battery negative electrode sheet as described in claim 4, characterized in that, It also includes a lithium metal sheet, a Celgard 2400 separator, and an electrolyte; the lithium-ion battery negative electrode is the working electrode, and the lithium metal sheet is the counter electrode; the electrolyte has a concentration of 1 mol / L. The electrolyte is composed of ethylene carbonate and dimethyl carbonate in a 1:1 volume ratio.

6. A method employing the method described in claim 1 A sodium-ion battery anode sheet made of three-component mesoporous composite nanomaterials, characterized in that... It includes an aluminum foil current collector and an active material layer disposed on the surface of the aluminum foil current collector, the active material layer comprising the... The three-component mesoporous composite nanomaterial, conductive carbon black, and sodium carboxymethyl cellulose are present in a mass ratio of 7:2:

1.

7. A CR2032 type sodium-ion coin cell using the sodium-ion battery negative electrode sheet as described in claim 6, characterized in that, It also includes a sodium metal sheet, a glass fiber membrane, and an electrolyte; the sodium-ion battery negative electrode is the working electrode, and the sodium metal sheet is the counter electrode; the electrolyte has a concentration of 1 mol / L. The electrolyte is composed of ethylene carbonate and propylene carbonate in a 1:1 volume ratio, and contains 5% fluoroethylene carbonate by mass.

Citation Information

Patent Citations

  • MXene / MoS2 composite material for lithium ion battery anode

    CN109830675A

  • MoS2 / MXene / NF composite material and preparation and application thereof

    CN116334650A